2013
DOI: 10.1002/ajh.23477
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of revised IPSS cytogenetic risk stratification and prognostic impact of monosomal karyotype in 783 patients with primary myelodysplastic syndromes

Abstract: Cytogenetic classification by the revised international prognostic scoring system (IPSS-R) and the prognostic value of monosomal karyotype (MK) were assessed in 783 patients with primary myelodysplastic syndromes (MDS). At 22 months median follow-up, 562 (72%) deaths were recorded. Percentages of patients with IPSS-R "very good," "good," "intermediate," "poor," and "very poor" cytogenetic categories was 5, 63, 18, 4, and 10%, respectively. The corresponding median survivals were 21, 40, 24, 18, and 6.5 Intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
38
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 16 publications
6
38
0
Order By: Relevance
“…It was also possible that some unfavorable molecular alterations not detectable by chromosomal analysis were present in this group of patients and influence their survival. Similarly, Gangat et al [17] could not find the prognostic superiority of IPSS-R very good karyotype in a study of 783 patients with primary MDS and the prognosis among very good, intermediate, and poor cytogenetic categories seemed not different. In addition to AML [16], presence of MK was recently found to be a poor prognostic factor in MDS [18,19].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…It was also possible that some unfavorable molecular alterations not detectable by chromosomal analysis were present in this group of patients and influence their survival. Similarly, Gangat et al [17] could not find the prognostic superiority of IPSS-R very good karyotype in a study of 783 patients with primary MDS and the prognosis among very good, intermediate, and poor cytogenetic categories seemed not different. In addition to AML [16], presence of MK was recently found to be a poor prognostic factor in MDS [18,19].…”
Section: Discussionmentioning
confidence: 89%
“…In addition to AML [16], presence of MK was recently found to be a poor prognostic factor in MDS [18,19]. Patnaik et al [18] showed that MK could further identify a prognostically worse group in 127 patients with complex karyotype and Gangat et al [17] demonstrated MK adversely affected survival in both poor and very poor karyotype groups. In this study, we further showed that MK was significantly associated with shorter LFS and OS in the patients with IPSS-R poor and very poor cytogenetics as well as IPSS-R high and very high risk groups.…”
Section: Discussionmentioning
confidence: 99%
“…A Clinical Advisory Committee of ~100 hematologists, pathologists and cytogeneticists from all over the world has proposed incorporation of recent knowledge on cytogenetic and gene mutations detected in MDS [135]. In the proposed classification, MK is not considered as a specific MDS-subtype because of its controversial risk in presence or absence of CK [130,162]. Although the five-tier IPSS-R classification has incorporated most MK in the 'very poor' risk-group [9], further study is needed to determine its impact on prognosis independent of other cytogenetic and molecular mutations.…”
Section: Resultsmentioning
confidence: 99%
“…Monosomal karyotype is associated with high-risk MDS and adverse prognosis in some studies. 16 However, other studies have found that there is no significance of monosomal karyotype after accounting for complex karyotype (Ն3 or Ն5 independent abnormalities). 17 The new IPSS-R 5-group cytogenetic classification appears to account for most monosomal karyotype cases in its "very poor" risk group.…”
Section: Cytogenetics Mutation Analysis and Flow Cytometry Immunophementioning
confidence: 99%